Time delays and risk factors in the management of patients with active pulmonary tuberculosis: nationwide cohort study - Ko, Yousang; Min, Jinsoo; Kim, Hyung Woo; Koo, Hyeon-Kyoung; Oh, Jee Youn; Jeong, Yun-Jeong; Kang, Hyeon Hui; Kang, Ji Young; Kim, Ju Sang; Lee, Sung-Soon; Park, Jae Seuk; Kwon, Yunhyung; et al. (Scientific reports, 2022)
Estimating the time delay and identifying associated factors is essential for effective tuberculosis control. We systemically analysed data obtained from the Korea Tuberculosis Cohort in 2019 by classifying delays as presentation and healthcare delays of pulmonary tuberculosis (PTB). Of 6593 patients with active PTB, presentation and healthcare delays were recorded in 4151 and 5571 patients, respectively. The median presentation delay was 16.0 (5.0–40.0) days. Multivariable logistic regression analysis showed that longer presentation delays were associated with neuropsychiatric disease [adjusted odds ratio (OR) 2.098; 95% confidence interval (CI) 1.639–2.687; p < 0.001] and heavy alcohol intake (adjusted OR 1.505; 95% CI 1.187–1.907; p < 0.001). The median healthcare delay was 5.0 (1.0–14.0) days. A longer healthcare delay was associated with malignancy (adjusted OR 1.351; 95% CI 1.069–1.709; p = 0.012), autoimmune disease (adjusted OR 2.445; 95% CI 1.295–4.617; p = 0.006), and low bacterial burden manifested as an acid-fast bacillus smear-negative and tuberculosis polymerase chain reaction-negative status (adjusted OR 1.316; 95% CI 1.104–1.569; p = 0.002). Active case-finding programmes need to focus on patients with heavy alcoholism or neuropsychiatric diseases. To ensure early PTB detection, healthcare providers must carefully monitor patients with malignancy, autoimmune disease, or a high index of suspicion for PTB.